1992
DOI: 10.1557/proc-259-385
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning and Oxidation of Heavily Doped Si Surfaces

Abstract: HF-treated Si surfaces and the oxidation kinetics in pure water or in clean room air have systematically been studied by x-ray photoelectron spectroscopy (XPS). The oxidation of heavily-doped n-type Si appears to proceed parallel to the surface, resulting in the layer-by-layer oxidation. The oxide growth rate in pure water for heavily-doped n-type Si is significantly higher than that of heavily-doped ptype Si. This is explained by the electron tunneling from the Si conduction band to adsorbed O2 molecules to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…20 Though rinsing hydrogen terminated silicon surfaces with water is expected to destroy the hydrogen passivation, we observed that a quick water rinse after oxide removal followed by immediate transfer into the vacuum system of the evaporator did not impact the epitaxial growth of the nanowires. 21 Samples without any native oxide removal or samples left in air for 1-2 h between oxide removal and gold deposition showed random directions of nanowire growth indicating the reduction or absence of epitaxial growth due to the formation of native oxide on the silicon surface. It should be noted that the nanowire growth on these samples though not epitaxial, were still single crystalline and has been reported to predominantly grow with a ͗110͘ crystal orientation.…”
Section: Sample Preparationmentioning
confidence: 96%
“…20 Though rinsing hydrogen terminated silicon surfaces with water is expected to destroy the hydrogen passivation, we observed that a quick water rinse after oxide removal followed by immediate transfer into the vacuum system of the evaporator did not impact the epitaxial growth of the nanowires. 21 Samples without any native oxide removal or samples left in air for 1-2 h between oxide removal and gold deposition showed random directions of nanowire growth indicating the reduction or absence of epitaxial growth due to the formation of native oxide on the silicon surface. It should be noted that the nanowire growth on these samples though not epitaxial, were still single crystalline and has been reported to predominantly grow with a ͗110͘ crystal orientation.…”
Section: Sample Preparationmentioning
confidence: 96%
“…[1][2][3][4] As a result, it has been found that native oxide growth at room temperature needs both oxygen and water. 1 Secondly, native oxide grows on every monolayer ͑layer-by-layer oxidation͒ as determined by the change in native oxide thickness.…”
Section: Introductionmentioning
confidence: 99%
“…1 Secondly, native oxide grows on every monolayer ͑layer-by-layer oxidation͒ as determined by the change in native oxide thickness. 1,4 This suggests lateral oxidation from step edges on the silicon surface. 4 Thirdly, since the binding energy of the silicon-hydrogen ͑Si-H͒ bond is higher than that of the Si-Si bond, the initial stage of native oxide growth does not arise at the Si-H bonds at the top of the silicon surface but at the Si-Si back bonds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations